Identifikasi Keberadaan Bakteri Leptospira di Daerah Endemis Leptospirosis (Studi di Dukuh Kalitengah Kecamatan Wedi Kabupaten Klaten) - Ratnaningsih Ratnaningsih; Retno Hestiningsih; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Several regions in Indonesia are classified as leptospirosis endemic including Klaten Regency, which ranked 2nd highest case of leptospirosis in Central Java in 2018. Leptospirosis in human was transmitted by animals infected by the Leptospira bacteria, which rat was the main reservoir. This study aimed to identify rat reservoir to the existence of Leptospira bacteria in endemic areas.Methods: This study was an observational survey with cross sectional approach. The sample was rats caught by traps installed for 6 days in Dukuh Kalitengah, Kalitengah Village, Wedi Subdistrict, Klaten Regency in July 2019. The rats were identified and dissected to take their kidneys for laboratory testing using the Polymerase Chain Reaction (PCR) test to identity the existence of Leptospira bacteria.Result: The result showed that there were 17 rats and 6 Suncus murinus caught in 6 days and their species were Mus musculus (23.5%), Rattus tanezumi (41.2%), Rattus norvegicus (35.3%). The results of PCR test found 2 positive samples of Leptospira bacteria in Rattus tanezumi. Rattus tanezumi's habitat was close with humans in settlement areas where it can be a source of Leptospira infection and can spread to humans and other environments.Conclusion : The people in Dukuh Kalitengah are recommended to maintain the hygiene of their environment and improve their house’s sanitation so it not become nest and breeding grounds and also reduce the existence of rats.